Influence of Plant Variation for Treatment Train on Hydrologic Performance for Stormwater Runoff Treatment - Chin , Shou Xian (Universiti Teknologi PETRONAS, 2020)
Rapid urbanization leads to deterioration of water quality in the receiving stream. To overcome this, the treatment train that is made up of three bioretention cells is recommended. Due to the limitation of the research done for the identical treatment train, the relationship between the hydrological performance and plant variation as well as the inflow variation for the treatment train is still unknown. Therefore, the objectives of this study are to investigate the influence of inflow variation on the treatment train performance and to determine the hydrologic performance for treatment train with plants variation in proposed site. To achieve them, simulation of treatment trains is conducted by using 3 treatment train models to determine how the inflow variation and inflow variation affect the hydrological performance of treatment train. Different types of plants, which are no plant, Jasminum officinale and Cordyline fruticose are used in different treatment train. Different inflow rate, which are 0.4, 0.65 and 1 L/min are also used for the treatment trains with different plants.